Metabolic Potential, Ecology and Presence of Associated Bacteria Is Reflected in Genomic Diversity of Mucoromycotina - Muszewska, Anna; Okrasińska, Alicja; Steczkiewicz, Kamil; Drgas, Olga; Orłowska, Małgorzata; Perlińska-Lenart, Urszula; Aleksandrzak-Piekarczyk, Tamara; Szatraj, Katarzyna; Zielenkiewicz, Urszula; Piłsyk, Sebastian; Malc, Ewa; Mieczkowski, Piotr; et al. (Frontiers in Microbiology, 2021)
Mucoromycotina are often considered mainly in pathogenic context but their biology remains understudied. We describe the genomes of six Mucoromycotina fungi representing distant saprotrophic lineages within the subphylum (i.e. Umbelopsidales and Mucorales). We selected two Umbelopsis isolates from soil (i.e. U. isabellina, U. vinacea), two soil-derived Mucor isolates (i.e. M. circinatus, M. plumbeus), and two Mucorales representatives with extended proteolytic activity (i.e. Thamnidium elegans and Mucor saturninus). We complement computational genome annotation with experimental characteristics of their digestive capabilities, cell wall carbohydrate composition, and extensive total lipid profiles. These traits inferred from genome composition, e.g. in terms of identified encoded enzymes, are in accordance with experimental results. Finally, we link the presence of associated bacteria with observed characteristics. Thamnidium elegans genome harbours an additional, complete genome of an associated bacterium classified to Paenibacillus sp. This fungus displays multiple altered traits compared to the remaining isolates, regardless of their evolutionary distance. For instance, it has expanded carbon assimilation capabilities, e.g. efficiently degrades carboxylic acids, and has a higher diacylglycerol:triacylglycerol ratio and skewed phospholipid composition which suggests a more rigid cellular membrane. The bacterium can complement the host enzymatic capabilities, alter the fungal metabolism, cell membrane composition but does not change the composition of the cell wall of the fungus.Comparison of early-diverging Umbelopsidales with evolutionary younger Mucorales points at several subtle differences particularly in their carbon source preferences and encoded carbohydrate repertoire. Nevertheless, all tested Mucoromycotina share features including the ability to produce 18:3 gamma-linoleic acid, use TAG as the storage lipid and have fucose as a cell wall component.